2011
DOI: 10.1007/s00247-011-2005-7
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced sonography in pediatrics

Abstract: Microbubble US contrast agents are composed of an outer shell of protein, phospholipid or polymer that encase air or perfluorocarbon gas. These contrast agents have been widely used in adult cardiology patients to improve endocardial border delineation and have been proved safe and well tolerated in this patient population. There is also a growing body of literature elucidating the value of contrast-enhanced sonography to distinguish benign from malignant liver lesions in adults and to characterize non-hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 28 publications
(40 reference statements)
0
15
0
1
Order By: Relevance
“…of Pages 8 Transfontanellar contrast enhanced ultrasound in infants: Initial experience 7 a real-time bedside imaging modality, which can be repeated allowing easy follow-up and monitoring of brain lesions [21]. The theoretical benefits of IV contrast material injection during TFUS for brain analysis were described by McCarville [22]. In this review on the use of contrast enhanced sonography in pediatrics, the authors reported that the assessment of brain perfusion before the sequelae can be identified on conventional sonography.…”
Section: Discussionmentioning
confidence: 96%
“…of Pages 8 Transfontanellar contrast enhanced ultrasound in infants: Initial experience 7 a real-time bedside imaging modality, which can be repeated allowing easy follow-up and monitoring of brain lesions [21]. The theoretical benefits of IV contrast material injection during TFUS for brain analysis were described by McCarville [22]. In this review on the use of contrast enhanced sonography in pediatrics, the authors reported that the assessment of brain perfusion before the sequelae can be identified on conventional sonography.…”
Section: Discussionmentioning
confidence: 96%
“…This can be helpful in distinguishing between hyperemic/infl amed lymphoid tissue and normal tissue. The use of microbubble ultrasound contrast agents is still experimental and not routinely available for use in children [ 3 ]. The use of sonoelastography to measure the compressibility and elasticity of tissues-initially used in the evaluation of the liver-is presently under evaluation to determine tissue characteristics of superfi cial lymphoid structures in an effort to discriminate benign from neoplastic nodal enlargement [ 4 ].…”
Section: Ultrasoundmentioning
confidence: 99%
“…Alkalmazására számos területen lenne szükség gyermekkorban, hiszen drága, sok esetben altatással járó vizsgálatok kiválthatóak általa, például májtranszplantált gyermekeknél jelentősen megkönnyíti az arteria hepatica ábrá-zolását, amely Doppler-vizsgálattal az esetek egy részé-ben nem valósítható meg. Vesetranszplantált betegeknél a perfúzió ábrázolása segítséget jelent a rejectio korai észlelésében [8,9,10,11,12].…”
Section: öSszefoglaló Közleményunclassified